Human papillomavirus, human immunodeficiency virus, and esophageal squamous cell carcinoma in South Africa: a study of prevalence, co-infection, and risk factors - Mbatha, Sikhumbuzo Z.; Maphosho, Tania; Ramali, Dakalo; Damane, Botle; Nevhungoni, Portia; Mc-Cabe, Michelle; Mosoane, Benny; Hull, Rodney; Dlamini, Zodwa (Frontiers in Oncology, 2025)
BackgroundEsophageal squamous cell carcinoma (ESCC) is a serious public health concern in South Africa, ranking among the most lethal malignancies. It has known risk factors including human papillomavirus (HPV). HPV is strongly linked to squamous cell cancers (i.e., cervix, anus, and oropharynx) with human immunodeficiency virus (HIV) shown to increase susceptibility to HPV-related malignancies. The extent to which co-infection with these two viruses contribute to ESCC in South African populations is unclear. This study aimed to determine the prevalence of HPV and HIV in ESCC patients.MethodsA total of 78 ESCC patients were prospectively recruited between January 2022 and December 2024 at Steve Biko Academic Hospital, Pretoria, South Africa. Participants were assessed for HIV, and tumors biopsied by endoscopy. DNA was extracted from formalin-fixed paraffin-embedded (FFPE) tissue specimens and HPV detection and genotyping were performed. Statistical analyses were conducted using Stata 18, with chi-square tests and logistic regression applied to assess associations, using a significance threshold of p ≤ 0.05.Results and discussionThe study population was predominantly Black Africans (96%), 55% male and 45% female, and aged 34–86 years. HIV infection was present in 42.3% (n=33) of patients. High-risk HPV DNA was detected in 56.4% (n=44) of ESCC cases, with high-risk subtypes HPV16 and HPV18 being the most prevalent, found in 68% and 41% of HPV-positive cases, respectively. Co-infection with both HIV and HPV was observed in 23.1% (n=18) of patients. However, statistical analyses showed no significant association between HIV and HPV status in ESCC patients (p = 0.78). However, a trend towards correlation was noted between HIV status and HPV18 positivity (adjusted p = 0.051).ConclusionWhile no direct association between HIV and HPV in ESCC was found, the high prevalence of high-risk HPV, particularly HPV16 and HPV18, highlights the need for further research. Given South Africa’s burden of HIV and HPV, larger multicenter studies are essential to better understand viral contributions to esophageal carcinogenesis.